Understanding the determinants of purchase intention for halal cosmetics among gen Z / Shahira Abdul Jabar, Aidarohani Samsudin, Diana’ Mazan and Shashazrina Roslan - Abdul Jabar, Shahira; Samsudin, Aidarohani; Mazan, Diana’; Roslan, Shashazrina (UiTM Cawangan Johor, 2024)
This article aims to determine the factors influencing the purchase intention of halal cosmetics among Gen Z. The author applied the Theory of Reasoned Action (TRA) to ascertain the determinants influencing Gen Z's intention to purchase halal cosmetics. The predictors are subjective norms, attitudes, and religiosity. The study used a sample of 215 respondents from UiTM Cawangan Johor Kampus Segamat, and statistical analysis with SPSS was used to determine the significance of the impact of the independent factors. The results of the experiments show that attitudes, subjective norms, and religion positively and significantly influenced the intention to buy halal-certified cosmetics. Keywords: Gen Z, halal cosmetic, purchase intention